Bridging the Digital Divide: Making the Digital Economy Benefit to the Entire Society - Bin Zhang; Zhiye Jin; Zhidao Peng (International Telecommunications Society (ITS), 2018)
With the development of information technology, the connotation of the Digital Divide has evolved constantly. At present, we have entered the new era of "Digital Economy" and newer information technologies such as Big Data, Artificial Intelligence, Internet of Things, and Cloud Computing have been widely developed and applied. New technologies should also be included in the measurement of the Digital Divide. At the same time, the physical gap in traditional information technology has been greatly reduced. Under the condition that physical access conditions are similar, the gap in digital technology skills and use is highlighted. Under such circumstances, the measurement of the Digital Divide should be more concerned with Digital Literacy and Digital Experience. Under the background of the Digital Economy, the existence of the Digital Divide means that there is a huge first-mover advantage for the party at a more advanced position. Countries, regions and communities with faster information development will be able to use information dividends promptly to promote their own economic development. However, the party that is far lagging behind will have fewer opportunities to participate in the information-based Digital Economy. At the same time that economic development is at a disadvantage, because under the new economy condition, more work and social activities are closely related to information technology, therefore, opportunities for the information poor to participate in online education, training, entertainment, shopping and communication have also become fewer, and these have exacerbated social inequalities. In this study, qualitative analysis and quantitative analysis were used to study the Digital Divide evaluation system in the era of Digital Economy. In the qualitative part of this article, we summarize the definition of Digital Economy, the definition of Digital Divide and the measurement theory of regional Digital Divide by studying the literature, laying a solid theoretical foundation for the research of this article. Starting from the six aspects of Digital Technology Infrastructure, ICT Readiness, Economy Development, Government Innovation Support, Education and Digital Literature, Digital Contents and Applications, we put forward research hypotheses and build the corresponding evaluation system model. In the quantitative research part of this paper, empirical research methods were used to verify the hypothesis and model. Among them, through a large amount of domestic research data collected from China Statistical Yearbook, with SPSS statistical analysis software to process the data, this paper proposes a complete index system of informatization and Digital Divide evaluation in the Digital Economy era and weights distribution for the system, using Factor Analysis, Analytic Hierarchy Process and Expert Interview Methods. On this basis, this article understands the current situation of informatization development and regional Digital Divide by the calculation of the index. Through the Clustering Analysis and Average Deviation Analysis, we analyze the causes of the Digital Divide formation, understand the gap of regional informatization and digital development, and find the weakness in digital development. Then, we put forward some suggestions that can effectively improve bridging the Digital Divide to solve the "information gap", "knowledge division" and "rich and poor division" between regions due to the development and application level gap. It provides reference for bridging the Digital Divide and promoting regional information, economic and cultural balanced development. This will enable digital technology to be more utilized in the process of promoting the development of the Digital Economy. Giving full play to the connectivity of the Internet will allow the Digital Economy to benefit more regions and enhance the well-being of the entire society.
Keywords: 330; Digital Divide; Digital Economy; Evaluation Index System; Policy Suggestion